Improvement in childhood cancer survival in Lithuania over three decades - Rascon, Jelena; Smailytė, Giedrė (Acta medica Lituanica, 2020)
Background. Population-based EUROCARE-5 studies demonstrated that childhood cancer survival rates in Lithuania were 10–20% lower than the European mean. We aimed to analyse the change in the outcome of treatment of paediatric malignancies in Lithuania over 30 years. Methods. A single-centre retrospective analysis of children below 18 years of age treated for cancer at Vilnius University Hospital Santaros Klinikos between 1982 and 2011 was carried out. The minimal requirement of 5-year follow-up after diagnosis was specified for survival estimation. The vital status was assessed using data from the population-based Lithuanian Cancer Registry. To evaluate changes over time, the entire cohort was split into three groups according to the time of diagnosis: 1982–1991, 1992–2001, and 2002–2011. Results. A total of 1268 children met the inclusion criteria. The shortest median follow-up was 8.9 (IQR 6.4–11.5) years for patients treated in the third decade. The 5-year overall survival of the entire cohort increased from 37.3% (95% CI 30.2–44.3) in 1982–1991 to 70.7% (95% CI 66.4–74.1) in 2002–2011 (p < 0.0001). The same trend was evident when calculated separately for leukaemia (p < 0.0001), lymphoma (p < 0.0005), and solid tumours (p < 0.004). The percentage of cure rose from zero in the early years of the period analysed to 80% in 2010 and 2011. The improvement in the treatment outcome was attributable to the reduction of treatment-related mortality from 45.8% in 1982–1991 to 12.4% in 2002–2011 and disease recurrence from 30.4% to 19.6% for the same periods, respectively. Conclusions. Significant progress in the cure rate of children treated for cancer at our institution was observed over 30 years. Collaborative national and international clinical and research efforts are crucial to ensure further advances in care and cure.
Keywords: childhood cancer; survival; Lithuania